Culturally-Based Renewable Energy Media to Enhance Critical Thinking in Elementary Science Learning - Fitrianawati, Meita; Ainul Yaqin, Abid Rizal (Journal of Educational Technology Innovation and Applications, 2025)
This study investigates the effectiveness of renewable energy learning media, rooted in local culture, on enhancing the critical thinking skills of fifth-grade students at SD Muhammadiyah Demangan. Employing a quasi-experimental design, the research involved two groups: an experimental group that received the intervention using renewable energy-based media and a control group that followed conventional teaching methods. Data collection was conducted through pretest and posttest assessments. The findings revealed a significant improvement in the experimental group’s critical thinking skills, with the average posttest score rising from 58 to 80.6 (surpassing the minimum passing criteria of 75) compared to the control group’s average posttest score of 73. The results of the independent sample t-test indicated a significance value (2-tailed) of 0.018, confirming a statistically significant difference between the two groups. The study concludes that renewable energy learning media integrated with local cultural elements effectively improve students’ critical thinking abilities and can be a valuable innovation in primary education.